2003
DOI: 10.1074/jbc.m305687200
|View full text |Cite
|
Sign up to set email alerts
|

Development of Pure Prolactin Receptor Antagonists

Abstract: Prolactin (PRL) promotes tumor growth in various experimental models and leads to prostate hyperplasia and mammary neoplasia in PRL transgenic mice. Increasing experimental evidence argues for the involvement of autocrine PRL in this process. PRL receptor antagonists have been developed to counteract these undesired proliferative actions of PRL. However, all forms of PRL receptor antagonists obtained to date exhibit partial agonism, preventing their therapeutic use as full antagonists. In the present study, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
134
1
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 115 publications
(147 citation statements)
references
References 58 publications
10
134
1
2
Order By: Relevance
“…[15][16][17]33 First, results showing a beneficial effect of prolactin/prolactin receptor-targeted therapy in breast cancer have been reported from both in vitro and in vivo models using either pure prolactin receptor antagonists, such as D1-9-G129R-hPRL or D1-14-G129R-hPRL, or fusion peptides between a prolactin receptor antagonist and potential anti-tumor peptides, such as G129R-hPRL-IL2, G129R-hPRL-endostatin, or G129R-hPRL-PE40-KDEL. 12,[34][35][36] However, these drugs are in early stages of development and application, and difficulties regarding stability and binding affinity of prolactin receptor antagonist must be overcome before entering the clinic. 33 Nevertheless, a single clinical therapy trial using the anti-prolactinemic drug cabergoline combined with docetaxel in woman with metastatic breast cancer and concomitant hyperprolactinemia showed that tumor regression rate was significantly higher in patients treated with cabergoline than in those who received docetaxel alone.…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17]33 First, results showing a beneficial effect of prolactin/prolactin receptor-targeted therapy in breast cancer have been reported from both in vitro and in vivo models using either pure prolactin receptor antagonists, such as D1-9-G129R-hPRL or D1-14-G129R-hPRL, or fusion peptides between a prolactin receptor antagonist and potential anti-tumor peptides, such as G129R-hPRL-IL2, G129R-hPRL-endostatin, or G129R-hPRL-PE40-KDEL. 12,[34][35][36] However, these drugs are in early stages of development and application, and difficulties regarding stability and binding affinity of prolactin receptor antagonist must be overcome before entering the clinic. 33 Nevertheless, a single clinical therapy trial using the anti-prolactinemic drug cabergoline combined with docetaxel in woman with metastatic breast cancer and concomitant hyperprolactinemia showed that tumor regression rate was significantly higher in patients treated with cabergoline than in those who received docetaxel alone.…”
Section: Discussionmentioning
confidence: 99%
“…Taking together these observations we can suggest that local manipulation of JAK-STAT activation can be a very perspective therapeutic approach for managing of cholangiocarcinoma at different stages of its progression. Recent advances in development of hormonal and cytokine antagonists (recombinant proteins for Prl and GH and peptide for IL-6 [145][146][147] ) give us an efficient tool for this treatment. Since synthetic specific inhibitors of JAK and other tyrosine kinases are intensively developed, we could suggest their efficient application for managing of cholangiocarinoma in addition to antagonists.…”
Section: Perspective Therapeutic Addressing Of the Jak-stat Pathwaymentioning
confidence: 99%
“…Tyrphostin B42 (AG490) is a pharmacological inhibitor of JAK2 activity and Del1-9-G129R-hPrl is a specific, competitive PrlR antagonist (18). Both inhibited constitutive phosphorylation of PrlR I146L stably expressed in HEK cells (Fig.…”
Section: Inhibition Of Prlri146l Constitutive Activity By Prlr Signalmentioning
confidence: 99%